Analysis on Green Building Design in China. Issue 1 (July 2021) - Zhou, Junhua; Ye, Yingjuan
Abstract: With the acceleration of urbanization in China, urban development is facing a huge ecological environment crisis, so it is urgent to promote the construction of green buildings. This paper first introduces the concept and standard of green building, then summarizes the main characteristics of green building, and finally puts forward the main points of green building design, hoping to provide a useful reference for the future green building design in China.